THE RELATIONSHIP BETWEEN DEMOGRAPHIC FACTORS AND LECTURERSâ EFFICACY BELIEFS IN PROJECT-BASED LEARNING - A. Rahim, Sakhiyyah (Proceeding 7th International Seminar on Regional Education, 2015)
AbstrakThis study attempted to investigate the relationship between demographic factors (gender, academic qualification, teaching hours and formal training received) and lecturersâ efficacy beliefs in project-based learning (pbl). A validated scale consisting of 9 items measuring lecturersâ efficacy beliefs in pbl was administered to 354 lecturers in the 23 Teacher Education Institutes (TEI) in Malaysia. In this study, structural equation model approach was used to explain the interactions between the demographic variables and lecturersâ efficacy beliefs in PBL. Significant direct interactions were found between (1) academic qualification and efficacy beliefs in pbl, and (2) Formal Training and efficacy belief. Gender and teaching hour meanwhile did not generate any significant relationship.These findings reaffirmed the past findings stating that two factors affected PBL which could be classified into two broad categories: (a) teacher/lecturer personal factors and (b) school/institution contextual factors.Keywords: demographic factors, efficacy beliefs, project-based learning, structural equation model